Analisis Teknik Kebutuhaan Alat Gali Muat dan Alat Angkut Menggunakan Simulasi Teori Antrian Pada Produksi Batu Kapur Area Eksisting 206 PT Semen Padang (Persero) TBK. - Hari Sentosa; Sumarya Sumarya; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. PT. Semen Padang owned by the unions, located at Indarung Padang,West Sumatera The hour barriers based on report operations tool tools digging and hauling of period may 2017 PT Semen Padang. that is, digger  tool  7,15 hours and hauler tools 7,46. Based on the study of the hour 4,2 hours. PT. Semen Padang Target of production and realization at a Eksisitng 206 may 2017 year the target of 320 Ton/hour for 1 unit of dump trucks, based on the analysis of the realized 282,31 Tons/hour, while based on the study of the production of obtained 363,58 tons/hour. Based on observations in field, conditions of work and the front area dumping still experiencing queue. The availability of tools and tool unloading hauler at a area 206 existing excavators serve the 6 units of dump trucks. Match factor of actual field is 1,18. Based on a review of the results of the productivity gained 1 unit excavators serve the 5 units of dump trucks and based on the theory of queues device used tool transport 5 units of dump trucks. As for the correction factor in the match after having examined 0,99 or close to 1.Keywords: Abstract. PT. Semen Padang owned by the unions, located at Indarung Padang,West Sumatera The hour barriers based on report operations tool tools digging and hauling of period may 2017 PT Semen Padang. that is, digger  tool  7,15 hours and hauler tools 7,46. Based on the study of the hour 4,2 hours. PT. Semen Padang Target of production and realization at a Eksisitng 206 may 2017 year the target of 320 Ton/hour for 1 unit of dump trucks, based on the analysis of the realized 282,31 Tons/hour, while based on the study of the production of obtained 363,58 tons/hour. Based on observations in field, conditions of work and the front area dumping still experiencing queue. The availability of tools and tool unloading hauler at a area 206 existing excavators serve the 6 units of dump trucks. Match factor of actual field is 1,18. Based on a review of the results of the productivity gained 1 unit excavators serve the 5 units of dump trucks and based on the theory of queues device used tool transport 5 units of dump trucks. As for the correction factor in the match after having examined 0,99 or close to 1.Keywords:  Digging and hauling; Hour barriers; Production; Match Factor; Queue